Editorial: ticks & tick-borne parasites and diseases - Ala E. Tabor; Ala Tabor (Parasitology)
Ticks and tick-borne diseases affect humans, livestock, and wildlife in most regions of the globe. Although there are over 900 tick species globally, only approximately 10% of species are second to mosquitoes as major vectors of human and veterinary diseases. The 17 articles of this themed Special Issue highlight the current research trends associated with newly discovered tick species, concepts of tick evolution, new vaccinology approaches, factors affecting disease transmission, and factors affecting tick ecology and tick-borne disease epidemiology. Table 1 summarizes the articles in this Special Issue in alphabetical author order and Fig. 1 is a word cloud generated from the article titles. Of the 17 articles in this Special Issue, two are review articles (vaccinology) while the remaining 15 are original research articles. The topics range from tick control, to epidemiology, ecology, tick-borne disease control, tick-borne disease transmission, vaccine approaches, and the description of novel extant and extinct tick species. Fig. 2 is graphical representation of the articles within this Special Issue including tick hosts and the most representative tick species studied. The articles also include authors from most continents globally with first author contributions from Australia, Bangladesh, Brazil, Czech Republic, Germany, India, Mexico, Pakistan, South Africa, Spain, Turkey, United Arab Emirates, USA and Zambia. This issue is thus truly diverse which reflects the diversity of ticks, tick-borne diseases and they hosts they infest globally.